Omenn syndrome: a case report and review of literature - Chia-Chi Hsu; Julia Yu-Yun Lee; Sheau-Chiou Chao (Wolters Kluwer Medknow Publications, 2011)
Exfoliative dermatitis or erythroderma in infancy is rare. Clinicians need to be alert to the possible diagnosis of Omenn syndrome (OS), a rare form of combined immunodeficiency in infants presenting with recurrent infections, erythroderma, lymphadenopathy, hepatosplenomegaly, eosinophilia, and increased serum IgE levels. OS is fatal unless treated by hematopoietic stem cell transplantation. We described a 26-day-old boy who had presented with diffusely thick scales on the scalp and some pustules on his face and trunk since birth. The rash was initially treated as presumed seborrheic dermatitis. At the age of 42 days, he developed extensive exfoliative dermatitis, lymphadenopathy, hepatosplenomegaly, and failure to thrive as well as eosinophilia and increased serum IgE levels. The histopathology of the skin and lymph node were consistent with the diagnosis of OS. He had been prepared for allograft bone marrow transplantation twice at 5 months and 7 months of age, but the procedure was not performed because of catheter-related sepsis. The patient eventually died of sepsis secondary to perianal cellulitis at 20 months of age.